Bioprocess development for biolubricant production using microbial oil derived via fermentation from confectionery industry wastes. (November 2018) - Papadaki, Aikaterini; Fernandes, Keysson Vieira; Chatzifragkou, Afroditi; Aguieiras, Erika Cristina Gonçalves; da Silva, José André Cavalcanti; Fernandez-Lafuente, Roberto; Papanikolaou, Seraphim; Koutinas, Apostolis; Freire, Denise Maria Guimarães
Highlights: Biolubricant production from microbial oil derived from food industry waste. Solvent-free enzymatic catalysis was employed for biolubricant production. The highest conversion yield of neopentyl glycol esters was 88%. The highest conversion yield of trimethylolpropane esters was 83%. Esters from microbial oil showed promising lubricant properties. Abstract: Microbial oil produced from confectionery and wheat milling side streams has been evaluated as novel feedstock for biolubricant production. Nutrient-rich fermentation media were produced by a two-step bioprocess involving crude enzyme production by solid state fermentation followed by enzymatic hydrolysis of confectionery industry waste. Among 5 yeast strains and 2 fungal strains cultivated on the crude hydrolysate, Rhodosporidium toruloides and Cryptococcus curvatus were selected for further evaluation for biolubricant production based on fermentation efficiency and fatty acid composition. The extracted microbial oils were enzymatically hydrolysed and the free fatty acids were esterified by Lipomod 34-MDP in a solvent-free system with trimethylolpropane (TMP) and neopentyl glycol (NPG). The highest conversion yields were 88% and 82.7% for NPG esters of R. toruloides and C. curvatus, respectively. This study also demonstrates that NPG esters produced from microbial oil have promising physicochemical properties for bio-based lubricant formulations that could substitute for conventional lubricants.